Soil-grapevine Interactions: Insight from Verdicchio in the Marche Wine Region, Italy - (:unkn) unknown (My University, 2017)
Verdicchio is a white grape varietal notably grown in the Marche wine region of east-central Italy within two Denominazione Origine Controllata (DOCs); Castelli di Jesi and Matelica, located less than 50 km apart. Jesi lies in the Apennine foothills near the coast of the Adriatic Sea and produces a smooth wine noted with apple-pear undertones and crisp, clean acidity. Conversely, Matelica is located in a synclinal valley of a fold-and-thrust belt and produces stronger wine with penetrating floral aromas and bold acidity. While macro-climatic variations do exist between DOCs, this research focuses on geological variations, specifically variations in soil composition, and understanding how geology could affect the grapevine nutrient supply contributing to the distinct wine flavor characteristics noted between DOCs. In order to quantify variations in both soil and plants between DOCs, several soil and plant analyses were conducted. This study focused upon soil samples collected within eight vineyards, with a total of ten soil profiles, and ten grapevine stem samples collected next to each soil profile. Soil samples were analyzed for soil texture, pH, organic matter, mineralogy, elemental and oxide concentrations, plant available nutrients, base saturation, cation exchange capacity, macronutrient element concentrations (N, C, and P), and N isotopes (𝛿15N). Grapevine stem samples were also analyzed for macronutrient elements (N, C, and P) and N isotope composition (𝛿15N). The isotopic N ratios of grapevine stems and soil were used in a model to assess N turnover within the individual grapevine samples, assuming literature values for amino acid turnover. This study provides insight as to how soil variations could influence wine character through quantifying soil-grapevine interactions. I speculated that differences in N isotopes for both soil and plants between DOCs would reflect different biological processes, with primary focus on the biological processes occurring within grapevine stems. N isotope fractionation in grapevine stems were interpreted to reflect rates of amino acid synthesis as grapevine stems (woody tissue) are used as sites for amino acid storage. The N turnover model (related to amino acids) calculated that Jesi had double the N turnover in comparison to Matelica throughout the growing season. I interpreted this higher rate of amino acid synthesis within Jesi grapevine stems to be a direct result of mineralogical differences measured between the two DOCs. The majority of Jesi soil profiles were determined to have dolomite (CaMg(CO3)2), while Matelica soil profiles lacked dolomite. As a magnesium carbonate, dolomite most likely contributed to Jesi’s higher soil Mg concentrations in comparison to Matelica. Mg is an important soil macronutrient acting as the coordinating ion of chlorophyll as well as activating many enzymes needed for plant vitality. Jesi grapevine stems were also analyzed as having increased P concentrations, possibly further promoting Jesi’s plant energy metabolism. Jesi’s higher soil Mg concentration and higher grapevine stem P concentrations could impact plant metabolic processes such as chlorophyll synthesis as well as phenolic compound character, specifically tannins, which are known to influence wine character. Previous studies have correlated wine tannin characteristics to certain soil compositions. This study improves our understanding of how geological variations impact plant biological processes, and in turn, accounts for the flavor dichotomy noted between Verdicchio wine from both Jesi and Matelica.
Keywords: Dolomite; Grapevine; Soil; Tannins; Terroir; Wine